Analysis of Students’ Learning Interest on Online Learning in High School - Sholikah Indah Sari; Muhammad Asrori; Purwanti Purwanti (Universitas Tanjungpura, 2022)
Abstract The goal of this research was to understand more about the learning styles of high school students taking the online course. This was a descriptive technique to study that resembles a survey in certain respects. Social science students from 11th-grade serves as the research sample, with a total of 45 pupils being surveyed. Random sampling was used to draw the sample. Online learners are curious in data collection methods and technology, which attract their interest. Based on the results of data analysis on students' learning interest on online learning class as a whole reached 79.74% with the category